Health education initiatives within the Mental Health curricular extension in Nursing undergraduate studies: An experiential report (Research, Society and Development, 2023)
Objective: to report the students' experience regarding the planning, organization, and execution of workshops within the curricular extension in the university's Mental Health discipline, in the nursing course. Method: narrative of the workshop experiences within the curricular extension in the Mental Health discipline. Results: five student extensionists and one instructor from a private university's Nursing course participated, along with 50 individuals aged between 22 and 65, from a therapeutic community for psychoactive substance dependents in a city in northeastern Santa Catarina. Three meetings were held covering different topics. Activities were conducted, followed by feedback from the attendees for improvements and suggestions. Pedagogical strategies employed included interactive dynamics, educational games, and other techniques. The actions focused on anxiety, depression, and phobias. Final considerations: extension activities provide students with the link between theory and practice, fostering closeness between the university and society, aiming for mental health education geared towards social reintegration.